2015
DOI: 10.1111/apm.12424
|View full text |Cite
|
Sign up to set email alerts
|

S100A6 expression in cutaneous smooth muscle neoplasms

Abstract: The S100A6 protein is expressed in a variety of tissues and distinct staining patterns in S100A6 immunohistochemistry may be useful in the differential diagnosis of difficult lesions. We evaluated the staining pattern of the S100A6 antibody in 22 cases each of pilar leiomyoma (LM), angioleiomyoma (ALM), and cutaneous leiomyosarcoma (LMS). S100A6 labeled both the nucleus and cytoplasm of myocytes in positive cases. About 64% of LM and 86% ALM had positive staining to the S100A6 antibody but predominantly in a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…As previously mentioned, the expression of S100A2, S100A3, and S100A6 in pilomatrixoma is conducive to determining the source of cells in abnormally differentiated tissues [87]. According to the unique immunohistochemical staining mode of S100A6 antibody in columnar leiomyoma (LM), angioleiomyoma (ALM), and skin leiomyoma (LMS), it is helpful for the differential diagnosis between them: weak or no S100A6 staining supports the diagnosis of LM, whereas strong positive staining supports the diagnosis of LMS [88]. In addition, some studies have shown that the expression of S100A6 is significantly related to the malignant transformation of epidermal tumors, and the joint expression of S100A6 and MMP9 is related to the development of SCC [89].…”
Section: S100a6 In Skin Tumorsmentioning
confidence: 99%
“…As previously mentioned, the expression of S100A2, S100A3, and S100A6 in pilomatrixoma is conducive to determining the source of cells in abnormally differentiated tissues [87]. According to the unique immunohistochemical staining mode of S100A6 antibody in columnar leiomyoma (LM), angioleiomyoma (ALM), and skin leiomyoma (LMS), it is helpful for the differential diagnosis between them: weak or no S100A6 staining supports the diagnosis of LM, whereas strong positive staining supports the diagnosis of LMS [88]. In addition, some studies have shown that the expression of S100A6 is significantly related to the malignant transformation of epidermal tumors, and the joint expression of S100A6 and MMP9 is related to the development of SCC [89].…”
Section: S100a6 In Skin Tumorsmentioning
confidence: 99%
“…S100A6 was expressed in some skin smooth muscle tumors and the difference in staining intensity between LM and LMS was statistically significant. A strong S100A6 staining is conducive to the diagnosis of LMS, whereas negative staining supports the diagnosis of LM [ 89 ]. Moreover, S100A6 mRNA was significantly elevated in cholangiocarcinoma (CCA), while no significant increase was observed in hepatocellular carcinoma (HCC).…”
Section: Biomarker Role Of S100a6mentioning
confidence: 99%